A narrowing digital divide - Maya Forrester; Jonathan Matusitz (Communicare)
This paper analyses the effectiveness of the Internet as a tool for civic engagement among youth during the 2000, 2004, and 2008 US presidential elections. In this context, youth can be understood as the segment of the electorate comprised of individuals between the ages of 18 and 25 years. The authors apply concepts of the digital divide to address, hypothetically, the question of whether the Internet is the cure-all for political malaise among youth. As such, without the digital divide, would the Internet be able to resolve the issue of low political involvement among youth? This analysis concludes that the impact of the Internet on youth political participation has been demonstrated to be successful. The Internet has not only become a revolutionary and promising political communication medium and campaign tool, it is also a bulwark of democracy.